BIO-SYNTHESIS OF COPPER NANOPARTICLES FROM INDIGOFERA TINCTORIA LEAF - Kayode, Talabi Henry; Adewale, Esther Dolapo; Adewuyi, Benjamin Omotayo (UI Scholars Hub, 2024)
Leaf extracts are known to be rich in phytoconstituent biomolecules, making them a valuable source of medicinal compounds. They also serve as both capping and reducing agents in nanoparticle fabrication. A reaction between CuSO4.5H2O aqueous solution and the Indigofera tinctoria leaf extract results in the formation of stable copper nanoparticles. Phytochemical screening of the Indigofera tinctoria leaf extract revealed the presence of various compounds including carbohydrates, terpenoids, phenol, tannins, flavonoids, saponins, and glycosides in the sample. The biosynthesized copper nanoparticles (CuNPs) were subsequently subjected to various forms of analysis. Techniques used included UV–visible (UV–vis) spectroscopy, Fourier transform infrared spectroscopy (FTIR), and scanning electron microscopy. An observable change in the color of solutions from pale to thick brown indicated the formation of CuNPs. Further confirmation came from UV–vis spectroscopy, which established the production of CuNPs at 500 nm. FTIR analysis revealed that the CuNPs were covered by organic residues. The particles ranged from 210 nm to 260 nm as indicated from the SEM analysis.